0227 Using The Ihi Open School Chapter Model To Encourage Multiprofessional Collaboration In Patient Safety And Quality Improvement. (1st November 2014) - Simpson, Nicola; Robson, Wayne
Abstract : Background: The Institute for Health Improvement founded in the USA promotes and encourages multi-professional, multi-level working to improve Patient Safety.1 Description: A new chapter set up in Sheffield aims to facilitate student led initiatives and inter-disciplinary working 2 between medical students, student nurses and allied health professionals from both Sheffield Universities and staff from Sheffield Teaching Hospitals NHS Trust. Methodology: A core group of students have been recruited and a number of guest speaker led evening events have been held. The Sheffield Chapter has been promoted through both Universities and through social media, raising awareness of its presence and its ambitions. Student management is guided by a dedicated team of faculty. Potential impact: The Sheffield Chapter aims to grow and develop over the coming year. A full, varied calendar of events is planned and Sheffield is going to be host to a National IHI event in the Autumn. Future plans include collaboration with the University of Sheffield Medical Society, simulated patient based teaching, and development of links between students and audit projects at Sheffield Teaching Hospitals NHS Trust. Take home messages: Patient safety is fundamental to good healthcare practice. 3 The Sheffield Chapter aims to develop knowledge of this and multidisciplinary working across the undergraduate courses to breed a culture with a mature understanding of Patient Safety in tomorrows healthcare professionals. References: http://www.ihi.org/education/ihiopenschool/Pages/default.aspx http://www.sheffieldihichapter.co.uk http://www.patientsafetyfirst.nhs.uk/Content.aspx?path=/About-the-campaign/